Cu(OAc)2-Catalyzed Thiolation of Acyl C–H Bonds with Thiols Using TBHP as an Oxidant - Yuan, Yan-qin; Guo, Sheng-rong; Xiang, Jian-nan (Synlett, 2013)
Cu(OAc)2-promoted TBHP oxidative coupling reaction of formamides with thiols successfully proceeded through direct C–H bond activation of formamides. The corresponding S-phenyl dialkyl thiocarbamate compounds were formed with high yield under solvent-free conditions.
Keywords: TBHP; Cu(OAc)2; thiolation; thiols; formamide